Whole exome sequencing revealed a mutation in COL6A1 associated with ullrich congenital muscular dystrophy - Thao, Dinh Huong; Anh, Nguyen Phuong; Miyake, Noriko; Hai, Nong Van; Matsumoto, Naomichi; Duong, Nguyen Thuy (Vietnam Journal of Biotechnology, 2021)
Collagen type VI-related disorders consist of Ullrich congenital muscular dystrophies (UCMD) and Bethlem myopathy, in which these entities are at two opposite extremes of the phenotype continuum. Clinical characteristics include proximal joint contracture, distal joint hyperlaxity, generalized muscle weakness, normal cognitive function, and pulmonary insufficiency. Affected individuals have trouble standing up and walking independently. Mutations in 3 genes (COL6A1, COL6A2, and COL6A3) are associated with decreasing collagen-VI production and disrupting the microfibrillar network between skeletal muscles. In the present study, using whole-exome sequencing (WES), a pathogenic variant in the COL6A1 gene (NM_001848, c.868G>C, p.G290R) was detected in a Vietnamese family with UCMD patients. Segregation analysis by Sanger sequencing confirmed that this mutation was inherited in an autosomal dominant pattern. This study expands the breadth of congenital muscular dystrophies research landcape and underscores the efficiency of WES in investigating the etiology of this group of heterogeneous diseases. Insight about the underlying genetic causes could contribute to develop a well-timed treatment regimen and help patients make an informed decision about reproductive health.